Drosophila neuralized is a ubiquitin ligase that promotes the internalization and degradation of delta. - Lai, E.C.; Deblandre, G.A.; Kintner, C.; Rubin, G.M. (Developmental Cell, 2001)
The Drosophila gene neuralized (neur) has long been recognized to be essential for the proper execution of a wide variety of processes mediated by the Notch (N) pathway, but its role in the pathway has been elusive. In this report, we present genetic and biochemical evidence that Neur is a RING-type, E3 ubiquitin ligase. Next, we show that neur is required for proper internalization of Dl in the developing eye. Finally, we demonstrate that ectopic Neur targets Dl for internalization and degradation in a RING finger-dependent manner, and that the two exist in a physical complex. Collectively, our data indicate that Neur is a ubiquitin ligase that positively regulates the N pathway by promoting the endocytosis and degradation of Dl.